Hypothalamic–pituitary–adrenal axis in anorexia nervosa; an underestimated endocrine dysfunction among adolescents - Calcaterra, Valeria; Magenes, Vittoria Carlotta; Fratangeli, Nadia; Nigro, Giulia; Fabiano, Valentina; Mendolicchio, Leonardo; Zuccotti, Gianvincenzo (Frontiers in Pediatrics, 2024)
In patients affected by anorexia nervosa (AN) different endocrine abnormalities have been described, but, among them, hypothalamic-pituitary-adrenal (HPA) dysfunction, although associated to important side effects, is underestimated and has no therapeutical options. We present a narrative literature review to investigate the HPA axis in patients with AN, in order to highlight HPA dysfunction and its effects. We also described the crucial role of HPA monitoring, and to consider eventual therapeutic and preventive strategies in AN patients. The literature now available demonstrates that women and girls suffering from AN have higher measures of cortisol and lower levels of androgens as compared to controls. These endocrinological disturbances have deleterious effects on the subjects, both from the physical and from the psychological point of view. It's fundamental for physicians to consider these aspects when assessing AN patients. The mechanisms behind the adrenocortical dysfunctions in eating disorders patients remain an open question and there are no available treatments, thus research on this issue would be extremely useful and highly necessary, especially in the pediatric field.